2021
DOI: 10.1016/j.chest.2020.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Acute Care Hospitals Extend ICU Capacity for COVID-19 Response and Recovery

Abstract: The COVID-19 pandemic has presented novel challenges for the entire health-care continuum, requiring transformative changes to hospital and post-acute care, including clinical, administrative, and physical modifications to current standards of operations. Innovative use and adaptation of long-term acute care hospitals (LTACHs) can safely and effectively care for patients during the ongoing COVID-19 pandemic. A framework for the rapid changes, including increasing collaboration with external health-care organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 37 publications
1
16
0
6
Order By: Relevance
“…The prominent physical impairment and the need for prolonged ventilatory support also highlight the important role of LTACHs during the ongoing pandemic especially during periods of high acute ICU occupancy. To increase the available ICU resources in the regional acute care hospitals, our LTACHs developed an organizational model similar to what was recently described by Grigonis et al (16). The two LTACHs, having served the Chicago metropolitan area for more than 30 years, relied on the already well-established working relationships with regional acute care hospitals.…”
Section: Ltach Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The prominent physical impairment and the need for prolonged ventilatory support also highlight the important role of LTACHs during the ongoing pandemic especially during periods of high acute ICU occupancy. To increase the available ICU resources in the regional acute care hospitals, our LTACHs developed an organizational model similar to what was recently described by Grigonis et al (16). The two LTACHs, having served the Chicago metropolitan area for more than 30 years, relied on the already well-established working relationships with regional acute care hospitals.…”
Section: Ltach Outcomesmentioning
confidence: 99%
“…For those who survive, the duration of ventilatory support is prolonged (11,(13)(14)(15). When the clinical condition stabilizes, patients with COVID-19 receiving prolonged mechanical ventilation are commonly transferred to long-term acute care hospitals (LTACHs) for further care (16).…”
mentioning
confidence: 99%
“…Speaking about reducing the patient's decannulation time after tracheostomy, according to Hernández et al, 4 basing the decision to decannulate on suctioning frequency plus continuous high-flow oxygen therapy reduced the time to decannulation. In combination with the results of Kwak et al, 1 it could improve the treatment outcomes of patients with COVID-19.…”
Section: Shared Decision-making and Stakeholder Engagement In Covid-19 Tracheostomymentioning
confidence: 99%
“…Recent data have shown that LTACs are already playing a dual role as a substitute for ICU beds in regions with COVID-19 surges in addition to post-ICU partners in the continuum of care, and this may stretch already thin resources. 4 A recent study 5 suggested that the optimal timing of tracheostomy is between 13 to 17 days, highlighting that in the first 12 to 14 days, patients have either been liberated from mechanical ventilation or have not survived. Thus, waiting for approximately 2 weeks provides a clearer picture of a patient's course, and may prevent a procedure that later proves to be unnecessary.…”
Section: Shared Decision-making and Stakeholder Engagement In Covid-19 Tracheostomymentioning
confidence: 99%
“…Finally, postacute care networks traditionally have not been harnessed to handle high-acuity patients with COVID-19. Although there is a promise for long-term acute care hospitals (LTACHs) in this regard ( 4 ), current variations between individual institutions and regions, together with limited capacity, may make reliance on this model challenging.…”
mentioning
confidence: 99%